Biosensors - Micro and Nanoscale Applications 2015
DOI: 10.5772/60710
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Materials for Optical and Electrochemical Biosensors

Abstract: It is incontestable that the interactions and bonds that keep molecules united to generate unique supramolecular compounds, with individual properties, morphologies and behaviour, are of special dynamics and singular forces. Therefore, it is necessary to discuss and consider the types of interactions that may occur in a determined system, their dynamics and number, which directly act on the energetic balance that strengthen the union between participants and give rise to a supramolecule.In this chapter, a numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 70 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…Several examples of biosensors prepared with crude extracts as enzyme sources were reported [28][29][30]. Many studies aim to obtain less expensive biosensors with higher durability, since crude extracts mimic the natural enzyme environment.…”
Section: Crude Extracts As Enzyme Sources For Biosensing Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several examples of biosensors prepared with crude extracts as enzyme sources were reported [28][29][30]. Many studies aim to obtain less expensive biosensors with higher durability, since crude extracts mimic the natural enzyme environment.…”
Section: Crude Extracts As Enzyme Sources For Biosensing Applicationsmentioning
confidence: 99%
“…In addition, cofactors and coenzymes can be present in the crude extract. Martins et al [28] reported the preparation of a biosensor using the crude extract of the pumpkin Cucubita pepo for paracetamol detection in aqueous solution, and Benjamin et al [29] reported a biosensor prepared with a crude extract, which was a source of the polyphenol oxidase, anchored with cerium nanoparticles for rutin detection in solution, showing a limit of detection of the 0.16 μmol L −1 .…”
Section: Crude Extracts As Enzyme Sources For Biosensing Applicationsmentioning
confidence: 99%
“…The low energy barrier for disassembly and reassembly of supramolecular structure ( Li J. et al, 2020 ), specifically those that are based on aggregates held by π-π interactions, also support good signal amplification. Curently available supramolecular materials have been made from inorganic systems, organic structures, polymers, hybrid materials, charged molecules, crystals, gels, metallic nanoparticles, and others by combining various types of non-covalent interactions ( Martins et al, 2015 ; Wang et al, 2016 ). Many of these materials and their composites can be functionalized in a facile manner to achieve water solubility, making such supramolecular building blocks more relevant for sensing biological analytes under aqueous environments ( Wang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%